The dynamic effects of nutritional status on chemotherapy-related toxicity in patients with non-Hodgkin’s lymphoma - Zhou, Qian; Yang, HeXiang; Wang, Xinyue; Wang, LiHong; Yan, XueQian; Zhang, BeiRong; Ma, XueHong; Li, GuoHua; Li, JingLin; Zhang, JiaHui; Yan, ZhiHong; Bao, Ni; et al. (European journal of clinical nutrition, 2025)
Background/Objectives Understanding the dynamic changes in nutritional status of patients with non-Hodgkin’s lymphoma (NHL) during chemotherapy is crucial, as it significantly impacts chemotherapy-related toxicity and survival outcomes. Subjects/Methods This multi-center study included newly diagnosed NHL patients. Nutritional status and chemotherapy-related toxic effects were assessed over the first five chemotherapy sessions, with follow-ups conducted every 3 months. Patients were categorized into three groups based on pre-chemotherapy Patient-Generated Subjective Global Assessment (PG-SGA) scores: Group A (0–1), Group B (2–8), and Group C (>9). Repeated-measures ANOVA and Generalized Estimating Equations (GEE) models were used for analysis, with survival outcomes evaluated via Kaplan–Meier and Cox regression. Results A total of 143 patients (mean age 50.26 ± 15.02 years) completed the study, over a median follow-up of 18.8 months. PG-SGA scores were highest in Group C during chemotherapy ( P < 0.001), with significant time-group interaction effects ( P < 0.001). Liver and kidney impairments worsened across all groups ( P < 0.05), while gastrointestinal toxicity and bone marrow suppression initially decreased before increasing. GEE analysis showed that nutritional status positively influenced gastrointestinal toxicity ( β = 0.05, P = 0.001) and bone marrow suppression ( β = 0.04, P = 0.014). Malnourished patients exhibited worse pulmonary infection-free survival and overall survival ( P < 0.05). Conclusions NHL patients are highly susceptible to malnutrition during chemotherapy, which exacerbates chemotherapy-related toxicities, particularly gastrointestinal effects and myelosuppression. Maintaining good initial nutrition is vital for reducing toxicities and improving survival outcomes.